High incidence of PTSD diagnosis and trauma-related symptoms in a trauma exposed bipolar I and II sample - Hogg, Bridget; Valiente-Gómez, Alicia; Redolar-Ripoll, Diego; Gardoki-Souto, Itxaso; Fontana-McNally, Marta; Lupo, Walter; Jiménez, Esther; Madre, Mercè; Blanco-Presas, Laura; Reinares, María; Cortizo, Romina; Massó-Rodriguez, Anna; et al. (Frontiers in Psychiatry, 2022)
Background Post-traumatic stress disorder (PTSD) is an established comorbidity in Bipolar Disorder (BD), but little is known about the characteristics of psychological trauma beyond a PTSD diagnosis and differences in trauma symptoms between BD-I and BD-II. Objective (1) To present characteristics of a trauma-exposed BD sample; (2) to investigate prevalence and trauma symptom profile across BD-I and BD-II; (3) to assess the impact of a lifetime PTSD diagnosis vs. a history of trauma on BD course; and (4) to research the impacts of sexual and physical abuse. Methods This multi-center study comprised 79 adult participants with BD with a history of psychological trauma and reports baseline data from a trial registered in Clinical Trials (https://clinicaltrials.gov; ref: NCT02634372). Clinical variables were gathered through clinical interview, validated scales and a review of case notes. Results The majority (80.8%) of our sample had experienced a relevant stressful life event prior to onset of BD, over half of our sample 51.9% had a lifetime diagnosis of PTSD according to the Clinician Administered PTSD scale. The mean Impact of Event Scale-Revised scores indicated high levels of trauma-related distress across the sample, including clinical symptoms in the PTSD group and subsyndromal symptoms in the non-PTSD group. Levels of dissociation were not higher than normative values for BD. A PTSD diagnosis (vs. a history of trauma) was associated with psychotic symptoms [2(1) = 5.404, p = 0.02] but not with other indicators of BD clinical severity. There was no significant difference between BD-I and BD-II in terms of lifetime PTSD diagnosis or trauma symptom profile. Sexual abuse significantly predicted rapid cycling [2(1) = 4.15, p = 0.042], while physical abuse was not significantly associated with any clinical indicator of severity. Conclusion Trauma load in BD is marked with a lack of difference in trauma profile between BD-I and BD-II. Although PTSD and sexual abuse may have a negative impact on BD course, in many indicators of BD severity there is no significant difference between PTSD and subsyndromal trauma symptoms. Our results support further research to clarify the role of subsyndromic PTSD symptoms, and highlight the importance of screening for trauma in BD patients.